Collision prevention in Singapore Strait by using timed Petri net - Bošnjak, Rino; Kezić, Danko; Vidan, Pero; Kavran, Zvonko (Transport, 2020)
The problem of maritime traffic in Singapore Strait is traffic density, also the probability of collision, which is increased beside the existing Vessel Traffic System (VTS). The paper discusses the synthesis early warning system, or automatic crossing supervisor for Singapore Strait by using the Timed Petri Nets (TPN). Authors proposes dividing the strait in zones, so called crossings, where routes are crossing and in which the number of ships must be limited. The maximum number of vessels in period of time of the highest traffic density through the crossings are determined. Derived constraints are used for synthesis of crossing supervisor. The authors uses Petri nets to make model Singapore Strait, and use P-invariant method to syntheses crossing supervisor, which limits the number of ships in all critical crossings. Finally, the author verified derived supervisor by using Visual Object Net ++ programme for computer simulation. With the aid of Transas nautical simulator, the traffic in the strait is analysed. First published online 09 December 2019